AI intelligent induction graphene wallboard
By introducing functional microcapsules of modified graphene and far-infrared ceramic powder into graphene composite wall panels, a three-dimensional thermally conductive radiation network is constructed. Combined with an AI intelligent sensing system, the problem of interface peeling of traditional wall panels under hot and cold cycles is solved, achieving effective far-infrared radiation and promoting microcirculation, thus enhancing the application potential of wall panels in health and wellness buildings.
Patent Information
- Application Number
- CN202610099969.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-26
- Publication Date
- 2026-03-20
AI Technical Summary
Existing traditional graphene composite wall panels are prone to interfacial delamination under long-term hot and cold cycles, lack the ability to actively regulate the indoor microclimate and humidity environment, and cannot emit far-infrared rays that can penetrate human skin, thus limiting their in-depth application in the field of health and wellness buildings.
Functional microcapsules composed of modified graphene and far-infrared ceramic powder are constructed by grafting silane coupling agents and in-situ polymerization to build a three-dimensional thermally conductive and radiative network. Combined with an AI intelligent sensing system to monitor the preparation process, the material is uniformly dispersed in the polymer matrix, thereby achieving far-infrared radiation and promoting microcirculation.
It significantly reduces the agglomeration of functional fillers, improves the thermal conductivity and far-infrared response speed of the material, promotes the increase of subcutaneous temperature, improves microcirculation and physiotherapy functions, and enhances the overall performance of the wall panel.
Smart Images

Figure CN121699378A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional building materials technology, and in particular to an AI intelligent sensing graphene wall panel. Background Technology
[0002] The field of functional building materials technology encompasses the application of chemical modification or physical composite methods to impart specific physicochemical properties to building panels. Among these, traditional graphene composite wall panels with far-infrared functionality refer to panels made by simply physically blending graphene powder and conventional mineral fillers into a polyvinyl chloride or wood-plastic composite matrix, and then preparing them through extrusion or calendering processes. These panels typically utilize the thermal conductivity of graphene to aid heat dissipation and rely on the inherent radiation properties of the mineral fillers to achieve a certain degree of infrared emission.
[0003] Traditional wall panel materials in the present technology only have basic decorative and physical partition functions. Their internal filler and matrix interface have poor compatibility, which makes the material prone to interface peeling or micro-crack propagation under long-term hot and cold cycles. Moreover, such materials lack the ability to actively regulate the indoor microclimate temperature and humidity environment, and cannot emit far-infrared rays of specific wavelengths that can penetrate human skin. It is difficult to produce a positive promoting effect on the human microcirculation system through physical environmental intervention, which limits their in-depth application in the field of health and wellness buildings. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of existing technologies by proposing an AI-powered intelligent sensing graphene wall panel.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: a graphene composite wall panel, wherein the materials used to prepare the graphene composite wall panel include: (a) 40-60 parts by weight of polyurethane resin matrix; (b) 20-30 parts by weight of functional microcapsules, which are composed of modified graphene, octadecane phase change core material and far-infrared ceramic powder; (c) 5-10 parts by weight of flame retardant; (d) 2-5 parts by weight of processing aids. As a further aspect of the invention, the far-infrared ceramic powder comprises tourmaline powder and germanium powder, with a weight ratio of 1:1 to 2:1. The functional microcapsules have an average particle size of 10 to 20 micrometers. As a further aspect of the invention, the flame retardant is selected from one or a combination of two of ammonium polyphosphate or aluminum hydroxide; The processing aids include calcium stearate and polyethylene wax. As a further aspect of the present invention, the preparation method of the graphene composite wall panel includes the following steps: S1: Graphene oxide was dispersed in anhydrous ethanol, and silane coupling agent KH-570 was added. The modified graphene was obtained by ultrasonic treatment in a constant temperature water bath, grafting organic functional groups through silanization reaction, centrifugation and vacuum drying. S2: Using modified graphene as a stabilizer, octadecane phase change core material is emulsified in an aqueous phase, and a prepolymer solution containing tourmaline and germanium powder is added dropwise. A hybrid shell is constructed by in-situ polymerization to obtain functional microcapsules. S3: Add polyurethane resin matrix, functional microcapsules, and flame retardant to a twin-screw extruder, and... to At a certain temperature, the composite masterbatch is obtained by melt blending using screw shearing force, followed by die extrusion and pelletizing. S4: Fill the composite masterbatch into the preheated... Stainless steel molds, in The graphene composite wall panel is obtained by holding the pressure under pressure for 300 seconds for cross-linking and curing, followed by mold opening and cooling. As a further aspect of the present invention, the preparation process of the modified graphene includes: S11: Add graphene oxide powder to a three-necked flask containing anhydrous ethanol, and stir at 500 rpm for 30 minutes under the action of a mechanical stirrer to establish a graphene oxide dispersion. S12: Add silane coupling agent KH-570 dropwise to the graphene oxide dispersion, place the reaction system in a constant temperature water bath, turn on the ultrasonic generator with a frequency of 40 kHz for dispersion treatment, maintain the reaction for 2 hours, and obtain the grafting reaction suspension. S13: The grafting reaction suspension was separated into solid and liquid phases using a high-speed centrifuge at 10,000 rpm. The bottom precipitate was collected and washed three times with anhydrous ethanol. The modified graphene was dried in a vacuum drying oven for 12 hours. As a further aspect of the present invention, the preparation process of the functional microcapsules includes: S21: Modified graphene is added to deionized water and the pH value is adjusted to neutral. Molten octadecane phase change core material is added, and the mixture is sheared and dispersed for 15 minutes at a speed of 12,000 rpm using a high-shear emulsifier. A stable film is formed at the oil-water interface using the Pickering effect to obtain an oil-in-water emulsion. S22: Transfer the prepolymer solution containing tourmaline and germanium powder to a constant-pressure dropping funnel, and add it dropwise to an oil-in-water emulsion under stirring at a flow rate of 5 mL per minute, maintaining the system temperature at [temperature missing]. A mixed reaction system was obtained; S23: Heat the mixed reaction system to... The stirring speed was adjusted to 300 rpm, and the reaction was maintained at this temperature for 4 hours to complete interfacial condensation. After filtration, washing, and spray drying, functional microcapsules were obtained. As a further aspect of this invention, the preparation process of the composite masterbatch includes: S31: Add the polyurethane resin matrix, functional microcapsules, and flame retardant to a high-speed mixer according to the specified ratio. Premix at low speed for 10 minutes under ambient conditions to obtain premixed material; S32: The premixed material is added to the main feed port of a twin-screw extruder using a loss-in-weight feeder. The screw length-to-diameter ratio is set to 40:1, and the screw speed is controlled at 200 rpm. Shearing and melting are performed within the specified temperature range. The material is then extruded through a die, cooled in a water-cooling tank, and granulated using a pelletizer to obtain composite masterbatch. As a further aspect of this invention, the preparation process of the graphene composite wall panel includes: S41: Start the heating system of the flat vulcanizing machine to preheat the stainless steel mold to... Weigh out the measured amount of composite masterbatch and spread it evenly in the mold cavity, then close the mold cover. S42: Start the hydraulic system to apply The pressure is maintained for 300 seconds to complete the resin cross-linking and curing reaction. The mold cooling water circulation system is then activated to lower the mold temperature. The mold is opened and the product is ejected to obtain a graphene composite wall panel. As a further aspect of the present invention, the shell thickness control process of the functional microcapsules includes: The density of the octadecane phase change core material, the density of the hybrid shell formed by curing modified graphene and prepolymer, and the mass ratio of shell material to core material were obtained. The volume ratio of the shell to the core material is calculated based on the density and mass ratio, and the theoretical shell thickness of the functional microcapsule is derived by combining the droplet radius of the oil-in-water emulsion with the geometric volume relationship. By adjusting the dropping rate of the prepolymer solution based on the theoretical shell thickness, functional microcapsules with uniform particle size are obtained. As a further aspect of this invention, the preparation process of the prepolymer solution includes: melamine and A formaldehyde solution of a certain mass concentration was added to the reaction vessel at a molar ratio of 1:3. The pH was adjusted to 8.5 using triethanolamine. After stirring for 30 minutes, nano-sized tourmaline and germanium powder were added and ultrasonically dispersed to obtain a prepolymer solution.
[0006] Compared with the prior art, the advantages and positive effects of the present invention are as follows: In this invention, by grafting silane coupling agents onto the surface of graphene and growing nano-far-infrared ceramic particles in situ between its layers, a three-dimensional thermally conductive and radiative network with a high specific surface area is constructed. This significantly reduces the aggregation of functional fillers in the polymer matrix. The high thermal conductivity of graphene accelerates the endothermic and exothermic response of phase change microcapsules, while simultaneously exciting the ceramic particles to generate far-infrared bands that match the natural frequency of the human body. This effectively promotes the increase of deep subcutaneous temperature and dilates microvessels, realizing the function of wall panel materials in improving microcirculation and assisting in physical therapy. Attached Figure Description
[0007] Figure 1 This is a flowchart of a method for preparing a graphene composite wall panel according to the present invention. Detailed Implementation
[0008] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the technical solutions of this invention and do not constitute a limitation on the scope of protection.
[0009] In the description of this invention, the process flow relationships or material and energy transfer paths indicated by terms such as "unit," "step," "equipment," "pipeline," "material flow," and "process parameters" are defined based on the process flow diagram or equipment structure diagram corresponding to the embodiments. This way of expression is only used to clearly illustrate the logical relationship between the elements in the technical solution, and not to limit the specific equipment connection method or physical layout. The term "multiple" includes two or more technical units, including but not limited to multiple reactors, pumps, valves, separation units, or detection instruments and other expandable elements. The specific number is determined according to specific process requirements or production scale and needs to be specifically stated.
[0010] Example 1 In this embodiment, the raw material formulation and process parameters are strictly set according to the minimum values of the range described in the claims, and an AI intelligent sensing system is introduced to monitor and provide closed-loop feedback on key parameters throughout the entire process in real time. Specific parameters are as follows: the amount of polyurethane resin matrix is 40 parts by weight (set as 40 kg), the amount of functional microcapsules is 20 parts by weight (set as 20 kg), the amount of flame retardant is 5 parts by weight (set as 5 kg), and the amount of processing aid is 2 parts by weight (set as 2 kg). The weight ratio of tourmaline powder to germanium powder in the far-infrared ceramic powder is set to 1:1. The target average particle size of the functional microcapsules is set to 10 micrometers (i.e., a droplet radius of 5 micrometers). The treatment temperature of the silane coupling agent KH-570 is 60°C, and the ultrasonic treatment time is 2 hours. The temperature of each section of the twin-screw extruder is uniformly controlled at 180°C. The die preheating temperature is 150°C, the holding pressure is 15 MPa, and the holding time is 300 seconds.
[0011] Please see Figure 1 This invention provides a technical solution: a method for preparing an AI intelligent sensing graphene composite wall panel, comprising the following steps: S1: Graphene oxide was dispersed in anhydrous ethanol, and silane coupling agent KH-570 was added. The modified graphene was obtained by ultrasonic treatment in a constant temperature water bath, grafting organic functional groups through silanization reaction, centrifugation and vacuum drying. The preparation process of modified graphene specifically includes: S11: Add graphene oxide powder to a three-necked flask containing anhydrous ethanol, and stir at 500 rpm for 30 minutes under the action of a mechanical stirrer to establish a graphene oxide dispersion. S12: Add silane coupling agent KH-570 dropwise to the graphene oxide dispersion, place the reaction system in a constant temperature water bath, turn on the ultrasonic generator with a frequency of 40 kHz for dispersion treatment, maintain the reaction for 2 hours, and obtain the grafting reaction suspension. S13: The grafting reaction suspension was separated into solid and liquid phases using a high-speed centrifuge at 10,000 rpm. The bottom precipitate was collected and washed three times with anhydrous ethanol. The modified graphene was obtained by drying it in a vacuum drying oven for 12 hours.
[0012] The first step is to prepare the modified graphene. The operator activates a precision electronic balance connected to the AI-powered intelligent weighing module of the central control system, weighs the graphene oxide powder, and places it in a clean stainless steel hopper. The vacuum conveying system is then activated to quantitatively deliver the graphene oxide powder into a reaction vessel pre-filled with anhydrous ethanol solvent, the volume of which is adjusted according to a solid-liquid ratio of 1:100. The mechanical agitator at the top of the reaction vessel is then activated, with the impeller speed set to 500 rpm, and stirring continuously for 30 minutes. During this time, the rheological properties of the dispersion are monitored in real time using an online viscometer and its integrated AI-powered intelligent rheological analysis unit. This unit intelligently identifies changes in the dispersion state until the dispersion exhibits a uniform dark brown color and no visible suspended particles are present.
[0013] Subsequently, silane coupling agent KH-570 was slowly added dropwise into the reactor using a constant-pressure dropping funnel at a rate controlled at 5 ml / min. The dropping process was calibrated in microseconds by an AI intelligent flow meter. Simultaneously, the water bath circulation system in the reactor jacket was activated, and the circulating water temperature was set and stabilized at 60.0℃. After the temperature sensor reading stabilized, the built-in ultrasonic generator was turned on, with the ultrasonic frequency set to 40 kHz and the power density to 0.5 W / cm², to perform continuous ultrasonic cavitation treatment on the reaction system for 2 hours. During this period, the AI intelligent sound field monitoring probe captured the cavitation noise spectrum in real time to ensure uniform cavitation effect distribution. After ultrasonic treatment, the grafted reaction suspension was transported to a high-speed tubular centrifuge using a diaphragm pump, and solid-liquid separation was performed at a speed of 10,000 rpm. The separated supernatant was discharged into a waste liquid recovery tank, and the sediment at the bottom was automatically collected by a scraper and transferred to a washing tank. Fresh anhydrous ethanol was added for three countercurrent washes, each lasting 20 minutes. The washed filter cake was sent to a vacuum drying oven, with the internal pressure set at -0.09 MPa, the temperature at 60°C, and the drying time set at 12 hours. After drying, the product was pulverized using an air jet mill to obtain dried modified graphene powder.
[0014] The aforementioned ultrasonic cavitation treatment refers to the physical process that utilizes the tiny bubbles generated when high-frequency sound waves propagate in a liquid. These bubbles form in the negative pressure zone of the sound waves and collapse rapidly in the positive pressure zone, thereby creating a high-temperature and high-pressure environment in the microscopic local area to promote the chemical reaction rate and improve the dispersion effect.
[0015] S2: Using modified graphene as a stabilizer, octadecane phase change core material is emulsified in an aqueous phase, and a prepolymer solution containing tourmaline and germanium powder is added dropwise. A hybrid shell is constructed by in-situ polymerization to obtain functional microcapsules. The far-infrared ceramic powder includes tourmaline powder and germanium powder, and the weight ratio of the two is 1:1 to 2:1. The average particle size of the functional microcapsules is 10 to 20 micrometers; The preparation process of the prepolymer solution includes: melamine and A formaldehyde solution of a certain mass concentration was added to the reaction vessel at a molar ratio of 1:3. The pH was adjusted to 8.5 using triethanolamine. After stirring for 30 minutes, nano-sized tourmaline and germanium powder were added and ultrasonically dispersed to obtain a prepolymer solution. The preparation process of functional microcapsules specifically includes: S21: Modified graphene is added to deionized water and the pH value is adjusted to neutral. Molten octadecane phase change core material is added, and the mixture is sheared and dispersed for 15 minutes at a speed of 12,000 rpm using a high-shear emulsifier. A stable film is formed at the oil-water interface using the Pickering effect to obtain an oil-in-water emulsion. S22: Transfer the prepolymer solution containing tourmaline and germanium powder to a constant-pressure dropping funnel, and add it dropwise to an oil-in-water emulsion under stirring at a flow rate of 5 mL per minute, maintaining the system temperature at [temperature missing]. A mixed reaction system was obtained; S23: Heat the mixed reaction system to... The stirring speed was adjusted to 300 rpm, and the reaction was kept at the temperature for 4 hours to complete the interfacial condensation. After filtration, washing with water and spray drying, functional microcapsules were obtained. The process of controlling the shell thickness of functional microcapsules includes: The density of the octadecane phase change core material, the density of the hybrid shell formed by curing modified graphene and prepolymer, and the mass ratio of shell material to core material were obtained. The volume ratio of the shell to the core material is calculated based on the density and mass ratio, and the theoretical shell thickness of the functional microcapsule is derived by combining the droplet radius of the oil-in-water emulsion with the geometric volume relationship. By adjusting the dropping rate of the prepolymer solution based on the theoretical shell thickness, functional microcapsules with uniform particle size were obtained.
[0016] Next, the preparation of functional microcapsules and the control of shell thickness were carried out. The modified graphene prepared above was put into an emulsification kettle equipped with an online pH meter and an AI intelligent sensing acid-base balance prediction module. Deionized water was added, and 0.1 mol / L sodium hydroxide solution was added through an automatic titration pump. Based on the prediction of the titration curve by the AI intelligent sensing module, the pH value of the system was precisely adjusted to a neutral state of 7.0. The heating jacket was turned on to heat the aqueous phase to 50°C, and at the same time, the octadecane phase change core material, which had been preheated to a molten state (temperature 55°C) in the storage tank, was injected into the emulsification kettle through a metering pump.
[0017] The high-shear emulsifier was started, with the rotation speed set to 12,000 rpm and the shearing time to 15 minutes. During the shearing process, the modified graphene sheets spontaneously migrated to the oil-water interface under the Pickering effect, forming a stable oil-in-water emulsion. At this time, an AI intelligent sensing microscopic camera probe installed inside the reactor captured real-time images and analyzed the particle size distribution of the emulsion droplets. During this stage, technicians needed to perform theoretical calculations of the shell thickness and process control. The density value of the octadecane phase change core material was obtained (…). ), the density values of the hybrid shell formed by the curing of modified graphene and prepolymer ( And the mass ratio of shell material to core material (set to 1:4, i.e.) The average droplet radius of the current water-in-oil emulsion is obtained using the following formula in conjunction with feedback from the AI intelligent sensing probe. (corresponding to a diameter of 10 micrometers), the theoretical shell thickness of the functional microcapsule was derived and calculated. : in, The theoretical shell thickness representing the microcapsule. represents the radius of the core material droplet in the emulsion, Represents the quality of the shell material. Represents the quality of the core material. Represents the density of the core material, This represents the density of the shell material.
[0018] Substituting the above parameter values into the formula, the volume ratio of the shell to the core material is approximately 0.155, from which the theoretical shell thickness can be calculated. The thickness is approximately 0.25 micrometers. Based on this thickness value, the operator strictly sets the dropping rate of the prepolymer solution to 5 ml / min using an AI intelligent sensing control terminal to match the interfacial polymerization reaction kinetics. The prepolymer solution is prepared in a side-stream reactor by mixing melamine and a 37% formaldehyde solution at a 1:3 molar ratio, adjusting the pH to 8.5, and reacting at 70°C for 30 minutes. Then, nano-sized tourmaline and germanium powder (weight ratio 1:1) are added and ultrasonically dispersed. The prepolymer solution is then dropped into an emulsion maintained at 50°C. After the addition is complete, the reactor temperature is raised to 85°C, the anchor-type stirrer speed is adjusted to 300 rpm, and the reaction is maintained at a constant temperature for 4 hours. After the reaction, the slurry is filtered through a plate and frame filter press. The filter cake is washed with deionized water until neutral and then sent to a spray drying tower with an inlet air temperature of 180°C and an outlet air temperature of 80°C to collect functional microcapsules with an average particle size of 10 micrometers.
[0019] The Pickering effect mentioned above refers to the physicochemical phenomenon in which solid particles, instead of traditional surfactants, are irreversibly adsorbed at the oil-water interface to form a tightly packed particle film, thereby effectively preventing droplet aggregation and giving the emulsion extremely high stability.
[0020] S3: Add polyurethane resin matrix, functional microcapsules, and flame retardant to a twin-screw extruder, and... to At a certain temperature, the composite masterbatch is obtained by melt blending using screw shearing force, followed by die extrusion and pelletizing. The weight percentages of each component are as follows: 40-60 parts by weight of polyurethane resin matrix; 20-30 portions of functional microcapsules; 5-10 parts by weight of flame retardant; 2-5 parts by weight of processing aids; The flame retardant is selected from one or a combination of two of ammonium polyphosphate or aluminum hydroxide; Processing aids include calcium stearate and polyethylene wax; The preparation process of composite masterbatch specifically includes: S31: Add the polyurethane resin matrix, functional microcapsules, and flame retardant to a high-speed mixer according to the specified ratio. Premix at low speed for 10 minutes under ambient conditions to obtain premixed material; S32: The premixed material is added to the main feed port of the twin-screw extruder through a loss-in-weight feeder. The screw length-to-diameter ratio is set to 40:1, and the screw speed is controlled at 200 rpm. The material is sheared and melted within the temperature range, and then extruded through the die head, cooled in a water cooling tank, and granulated by a pelletizer to obtain composite masterbatch.
[0021] The compound masterbatch is then mixed and granulated. Operators use an automated batching system to add 40 kg of polyurethane resin matrix, 20 kg of functional microcapsules, 5 kg of flame retardant selected from ammonium polyphosphate, and 2 kg of processing aids consisting of 1 kg of calcium stearate and 1 kg of polyethylene wax to a high-speed mixer. The mixer is started, the low-speed agitator is set to 300 rpm, and the jacket heating is activated to raise the material temperature to 80°C. Premixing lasts for 10 minutes to ensure macroscopic uniform distribution of the components in the solid state. The mixing uniformity is determined online by an AI intelligent sensing spectral probe installed on the inner wall of the mixer.
[0022] The premixed material is transferred to the loss-in-weight feed hopper of a twin-screw extruder via a vacuum feeder. The twin-screw extruder has a length-to-diameter ratio of 40:1, and the screw assembly uses an alternating configuration of high-shear conveying elements and kneading elements. The main screw speed is set to 200 rpm, and the extruder barrel is divided into ten temperature control zones. From the feed port to the die head, the temperature of each zone is uniformly set to 180℃. Each temperature control zone is equipped with an AI intelligent induction thermocouple, which can automatically optimize the heating power based on changes in the material's shear heat. Under the shearing and conveying action of the screw, the material undergoes melting, plasticizing, and dispersion. After impurities are filtered by a screen changer, the melt is extruded from a multi-hole die to form strips with a diameter of 3 mm. The melt strips immediately enter a circulating water cooling tank for quenching, with the water temperature controlled at 25℃. The cooled strips are dried by a blower to remove surface moisture, then cut into cylindrical particles by a cantilever pelletizer. After being screened by a vibrating screen to remove powder and conglomerates, uniformly sized composite masterbatch is obtained.
[0023] The above-mentioned melt blending refers to the process of mixing two or more polymers or additives in a fluid state heated above their melting point through mechanical shearing to achieve microscopic or macroscopic uniform mixing.
[0024] S4: Fill the composite masterbatch into the preheated... Stainless steel molds, in The pressure is held for 300 seconds to carry out cross-linking and curing. After mold opening and cooling treatment, graphene composite wall panels are obtained. The preparation process of graphene composite wall panels specifically includes: S41: Start the heating system of the flat vulcanizing machine to preheat the stainless steel mold to... Weigh out the measured amount of composite masterbatch and spread it evenly in the mold cavity, then close the mold cover. S42: Start the hydraulic system to apply The pressure is maintained for 300 seconds to complete the resin cross-linking and curing reaction. The mold cooling water circulation system is then activated to lower the mold temperature. The mold is opened and the product is ejected to obtain a graphene composite wall panel.
[0025] Finally, the graphene composite wall panel molding process is executed. The flatbed vulcanizing machine is started, and the electric heating system is activated to heat the stainless steel molds corresponding to the upper and lower pressure plates. The surface temperature of the stainless steel mold cavity is precisely stabilized at 150℃ through the mold temperature controller's circulating oil circuit. The operator weighs the specified weight of composite masterbatch and evenly spreads it inside the mold cavity, ensuring full filling of the edges and corners. The hydraulic control console is operated to control the upper mold's downward closing. The main hydraulic cylinder is activated, linearly increasing the mold closing pressure to 15MPa within 2 seconds. The pressure increase curve is precisely tracked by an AI intelligent sensing pressure controller to prevent stress concentration caused by sudden pressure changes. While maintaining a high pressure of 15MPa, a timer is started and maintained for 300 seconds. During this period, the polyurethane matrix and the functional groups on the microcapsule surface undergo a cross-linking and curing reaction, forming a molecular chain network structure.
[0026] After the pressure holding period, the mold temperature control system is immediately switched to cooling water circulation mode, rapidly reducing the mold temperature to 60°C at a rate of 20°C / minute. When the temperature sensor indicates that the mold temperature has reached 60°C, the hydraulic system is depressurized, and the upper mold is opened. The ejection mechanism is activated to eject the solidified graphene composite wall panel from the mold. A robotic arm picks up the panel and places it on a leveling rack to cool naturally to room temperature; simultaneously, the AI intelligent sensing vision inspection system quickly scans the surface of the freshly ejected panel to detect the presence of microcracks or pore defects, completing the manufacturing process.
[0027] Table 1 Monitoring Parameters for Prepolymer Solution Preparation Process ; As shown in Table 1, this table records the key process parameters in the prepolymer solution preparation stage, ensuring precise control of reaction conditions.
[0028] Table 2 Comparison of Product Performance in Example 1 ; As shown in Table 2, the graphene composite wall panel prepared in this embodiment is significantly superior to conventional polyurethane wall panels in terms of latent heat of phase change, flame retardancy and thermal conductivity.
[0029] Example 2 In this embodiment, the raw material formulation and process parameters are strictly set according to the maximum value of the range described in the claims, and the process parameters are also adaptively adjusted by relying on the AI intelligent sensing network. Specific parameters are as follows: the amount of polyurethane resin matrix is 60 parts by weight (60 kg), the amount of functional microcapsules is 30 parts by weight (30 kg), the amount of flame retardant is 10 parts by weight (10 kg), and the amount of processing aid is 5 parts by weight (5 kg). The weight ratio of tourmaline powder to germanium powder in the far-infrared ceramic powder is set to 2:1. The target average particle size of the functional microcapsules is set to 20 micrometers (i.e., droplet radius of 10 micrometers). The treatment temperature of the silane coupling agent KH-570 is 60℃ (constant temperature), and the ultrasonic treatment time is 2 hours (maintained consistently). The temperature of each section of the twin-screw extruder is uniformly controlled at 200℃. The die preheating temperature is 150℃, the holding pressure is 15 MPa, and the holding time is 300 seconds.
[0030] Please see Figure 1 This invention provides a technical solution: a method for preparing an AI intelligent sensing graphene composite wall panel, comprising the following steps: S1: Graphene oxide was dispersed in anhydrous ethanol, and silane coupling agent KH-570 was added. The modified graphene was obtained by ultrasonic treatment in a constant temperature water bath, grafting organic functional groups through silanization reaction, centrifugation and vacuum drying. The preparation process of modified graphene specifically includes: S11: Add graphene oxide powder to a three-necked flask containing anhydrous ethanol, and stir at 500 rpm for 30 minutes under the action of a mechanical stirrer to establish a graphene oxide dispersion. S12: Add silane coupling agent KH-570 dropwise to the graphene oxide dispersion, place the reaction system in a constant temperature water bath, turn on the ultrasonic generator with a frequency of 40 kHz for dispersion treatment, maintain the reaction for 2 hours, and obtain the grafting reaction suspension. S13: The grafting reaction suspension was separated into solid and liquid phases using a high-speed centrifuge at 10,000 rpm. The bottom precipitate was collected and washed three times with anhydrous ethanol. The modified graphene was obtained by drying it in a vacuum drying oven for 12 hours.
[0031] The preparation process of modified graphene in this embodiment is performed as follows: First, technicians prepare a clean reaction vessel and add 600 grams of graphene oxide powder to 60 liters of anhydrous ethanol. A high-power mechanical stirrer is started, set to a speed of 500 rpm, and pre-stirred at room temperature for 30 minutes to break up powder agglomeration. Then, the reaction vessel is placed in a constant-temperature water bath, and the water bath temperature is adjusted to 60.0°C and maintained constant. Sufficient silane coupling agent KH-570 is added to the system, and an industrial-grade ultrasonic disperser is turned on, setting the operating frequency to 40 kHz, to continuously subject the suspension to strong ultrasonic treatment for 2 hours. This process utilizes the localized high temperature and pressure generated by cavitation effect to promote the condensation reaction between the hydrolysis products of the silane coupling agent and the hydroxyl groups on the surface of graphene oxide. To ensure grafting efficiency, an AI intelligent sensing reaction monitoring instrument assesses the progress of the condensation reaction in real time by detecting changes in the conductivity of the reaction medium.
[0032] After the reaction was complete, the mixture was pumped into a tubular centrifuge and centrifuged at a high speed of 10,000 rpm for 15 minutes. The clarity of the supernatant was observed through a sight glass combined with an AI intelligent turbidity sensor. After confirming complete separation, the supernatant was discharged. The solid product was washed three times online with anhydrous ethanol in the centrifuge to completely remove unreacted silane monomers. The wet material was transferred to a vacuum drying oven and dried for 12 hours at 60°C and a vacuum of -0.095 MPa. The drying endpoint was automatically determined by an AI intelligent humidity sensor based on the exhaust humidity gradient. The dried filter cake was pulverized by an air jet mill and sieved through a 200-mesh sieve to obtain modified graphene powder. Infrared spectroscopy confirmed that organic functional groups had been successfully grafted onto the surface.
[0033] S2: Using modified graphene as a stabilizer, octadecane phase change core material is emulsified in an aqueous phase, and a prepolymer solution containing tourmaline and germanium powder is added dropwise. A hybrid shell is constructed by in-situ polymerization to obtain functional microcapsules. The far-infrared ceramic powder includes tourmaline powder and germanium powder, and the weight ratio of the two is 1:1 to 2:1. The average particle size of the functional microcapsules is 10 to 20 micrometers; The preparation process of the prepolymer solution includes: melamine and A formaldehyde solution of a certain mass concentration was added to the reaction vessel at a molar ratio of 1:3. The pH was adjusted to 8.5 using triethanolamine. After stirring for 30 minutes, nano-sized tourmaline and germanium powder were added and ultrasonically dispersed to obtain a prepolymer solution. The preparation process of functional microcapsules specifically includes: S21: Modified graphene is added to deionized water and the pH value is adjusted to neutral. Molten octadecane phase change core material is added, and the mixture is sheared and dispersed for 15 minutes at a speed of 12,000 rpm using a high-shear emulsifier. A stable film is formed at the oil-water interface using the Pickering effect to obtain an oil-in-water emulsion. S22: Transfer the prepolymer solution containing tourmaline and germanium powder to a constant-pressure dropping funnel, and add it dropwise to an oil-in-water emulsion under stirring at a flow rate of 5 mL per minute, maintaining the system temperature at [temperature missing]. A mixed reaction system was obtained; S23: Heat the mixed reaction system to... The stirring speed was adjusted to 300 rpm, and the reaction was kept at the temperature for 4 hours to complete the interfacial condensation. After filtration, washing with water and spray drying, functional microcapsules were obtained. The process of controlling the shell thickness of functional microcapsules includes: The density of the octadecane phase change core material, the density of the hybrid shell formed by curing modified graphene and prepolymer, and the mass ratio of shell material to core material were obtained. The volume ratio of the shell to the core material is calculated based on the density and mass ratio, and the theoretical shell thickness of the functional microcapsule is derived by combining the droplet radius of the oil-in-water emulsion with the geometric volume relationship. By adjusting the dropping rate of the prepolymer solution based on the theoretical shell thickness, functional microcapsules with uniform particle size were obtained.
[0034] Next, the functional microcapsules were synthesized and their size controlled. In a 200-liter reactor equipped with a pulping paddle, deionized water was added and modified graphene was dispersed. A precision pH meter and its accompanying AI intelligent sensor data logger were used for monitoring. Sodium hydroxide solution was added dropwise to stabilize the pH at 7.0. Preheated liquid octadecane phase change core material to 60°C was injected into the reactor; the amount of core material added was determined based on the final capsule wall material ratio. A high-shear dispersion emulsifier was started, set to a speed of 12,000 rpm, and subjected to high-speed shearing for 15 minutes to disperse the oil phase into micron-sized droplets. In this step, the shell thickness control logic was executed: the density of the octadecane phase change core material was obtained (…). ), hybrid shell density ( And the mass ratio of shell material to core material (set to 1:3, i.e.) ).
[0035] Using the geometric volume relationship logic detailed in the foregoing embodiments, the above physical parameters and the target droplet radius set in this embodiment and verified by the AI intelligent sensing particle size analyzer are combined. The volume ratio of the shell to the core material (corresponding to a diameter of 20 micrometers) was substituted into the calculation. During the calculation, the volume ratio of the shell to the core material was found to be approximately 0.207. Based on this volume ratio and the droplet radius, the theoretical shell thickness of the functional microcapsule was further calculated to be approximately 0.65 micrometers. According to this thickness value, the operator adjusted the valve opening of the prepolymer dripping pipeline, controlling the dripping rate to 5 ml per minute. The AI intelligent induction flow controller corrected minor flow rate deviations based on real-time feedback. The prepolymer was prepared by reacting melamine and formaldehyde at a 1:3 molar ratio at 70°C and pH 8.5, and mixed with tourmaline powder and germanium powder (nanoscale) at a weight ratio of 2:1. The prepolymer was dripped uniformly into the emulsion. After the dripping was complete, the temperature was increased to 85°C, the stirring speed was set to 300 rpm, and the mixture was kept at this temperature for 4 hours for curing. The reaction slurry was centrifuged, dehydrated, washed, and dried in a spray drying tower. The airflow speed in the tower was controlled to prevent capsule breakage, ultimately collecting microcapsule products with an average particle size of 20 micrometers.
[0036] S3: Add polyurethane resin matrix, functional microcapsules, and flame retardant to a twin-screw extruder, and... to At a certain temperature, the composite masterbatch is obtained by melt blending using screw shearing force, followed by die extrusion and pelletizing. The weight percentages of each component are as follows: 40-60 parts by weight of polyurethane resin matrix; 20-30 portions of functional microcapsules; 5-10 parts by weight of flame retardant; 2-5 parts by weight of processing aids; The flame retardant is selected from one or a combination of two of ammonium polyphosphate or aluminum hydroxide; Processing aids include calcium stearate and polyethylene wax; The preparation process of composite masterbatch specifically includes: S31: Add the polyurethane resin matrix, functional microcapsules, and flame retardant to a high-speed mixer according to the specified ratio. Premix at low speed for 10 minutes under ambient conditions to obtain premixed material; S32: The premixed material is added to the main feed port of the twin-screw extruder through a loss-in-weight feeder. The screw length-to-diameter ratio is set to 40:1, and the screw speed is controlled at 200 rpm. The material is sheared and melted within the temperature range, and then extruded through the die head, cooled in a water cooling tank, and granulated by a pelletizer to obtain composite masterbatch.
[0037] The preparation of the composite masterbatch is as follows: 60 kg of polyurethane resin, 30 kg of functional microcapsules, 10 kg of flame retardant (a compound of aluminum hydroxide and ammonium polyphosphate), and 5 kg of processing aids (calcium stearate and polyethylene wax) are sequentially added to a high-speed mixer through the feeding port. The equipment is started, the speed is set to 300 rpm, and heating is simultaneously activated. Mixing is performed at 80°C for 10 minutes to ensure sufficient contact between the high-filler-content microcapsules and the resin matrix. The mixture is then conveyed to the hopper of a twin-screw extruder via a screw feeder. In this embodiment, the extruder screw length-to-diameter ratio is set to 40:1, and the screw speed is maintained at 200 rpm. Given the high filler content, the barrel temperature is set to a higher 200°C (from the feeding section to the homogenization section) to reduce melt viscosity and improve flowability.
[0038] The material undergoes solid conveying, melting, venting, and homogenization processes within the barrel, with functional microcapsules uniformly dispersed within the polyurethane matrix. During this process, an AI-powered intelligent melt pressure sensor array continuously monitors the pressure build-up in each section of the barrel to prevent localized overpressure. After being extruded from the die, the melt strip enters a circulating water tank for cooling, and is then cut by a pelletizer to obtain high-content graphene composite masterbatch. Operators must periodically sample and test the melt flow index of the masterbatch to ensure its processing performance in subsequent molding processes.
[0039] S4: Fill the composite masterbatch into the preheated... Stainless steel molds, in The pressure is held for 300 seconds to carry out cross-linking and curing. After mold opening and cooling treatment, graphene composite wall panels are obtained. The preparation process of graphene composite wall panels specifically includes: S41: Start the heating system of the flat vulcanizing machine to preheat the stainless steel mold to... Weigh out the measured amount of composite masterbatch and spread it evenly in the mold cavity, then close the mold cover. S42: Start the hydraulic system to apply The pressure is maintained for 300 seconds to complete the resin cross-linking and curing reaction. The mold cooling water circulation system is then activated to lower the mold temperature. The mold is opened and the product is ejected to obtain a graphene composite wall panel.
[0040] Finally, the wall panel is hot-pressed. The upper and lower molds of the flat vulcanizing machine are preheated and stabilized at 150℃. Based on the mold cavity volume and material density, a sufficient amount of composite masterbatch is calculated and weighed. The masterbatch is evenly piled in the center and around the mold, and the mold is closed. The hydraulic system outputs pressure, rapidly raising the pressure inside the mold cavity to 15MPa and maintaining this pressure for 300 seconds. Under high temperature and high pressure, the polyurethane matrix fully flows and fills the mold details, undergoing a cross-linking reaction, while the microcapsules tightly bond with the matrix.
[0041] After the pressure holding process is completed, the system automatically switches to 15°C cold water for mold cooling, and monitors the mold temperature display. When the temperature drops to 60°C, the hydraulic press lifts the upper mold, and the ejector device ejects the formed wall panel. Operators wearing heat-resistant gloves remove the panel, inspect it for defects such as bubbles and cracks, and then stack it on the finished product rack. The entire molding cycle is coordinated by an AI intelligent sensing logic controller, ensuring real-time matching of mechanical actions with temperature and pressure parameters, thus improving production efficiency and yield.
[0042] Table 3. Operating Process Parameters of Twin-Screw Extruder ; As shown in Table 3, this table records the key equipment parameters of the twin-screw extruder under stable operating conditions, showing that the equipment load and melt state are both in the optimal processing window.
[0043] Table 4 Comparison of Product Performance in Example 2 ; As shown in Table 4, the product of Example 2 exhibits superior phase change heat storage capacity, flame retardancy, and mechanical properties with a higher amount of functional filler added. The above examples demonstrate preferred embodiments of the present invention. Any equivalent adjustments to the technical solution based on chemical engineering methods are within the scope of protection, including but not limited to: using different chemical reaction processes to achieve technical effects, optimizing the production process, adjusting raw material ratios, improving reactor design, and enhancing energy efficiency. Any implementation scheme derived from reasonable modifications to the production process, raw material utilization, equipment configuration, or system integration level without departing from the core technology of the present invention should be considered within the protection scope defined by the technical solution of the present invention.
Claims
1. A graphene composite wall panel, characterized in that, The materials used to prepare the graphene composite wall panel include: (a) 40-60 parts by weight of polyurethane resin matrix; (b) 20-30 parts by weight of functional microcapsules, which are composed of modified graphene, octadecane phase change core material and far-infrared ceramic powder; (c) 5-10 parts by weight of flame retardant; (d) 2-5 parts by weight of processing aids.
2. The graphene composite wall panel according to claim 1, characterized in that, The far-infrared ceramic powder includes tourmaline powder and germanium powder, and the weight ratio of the two is 1:1 to 2:
1. The average particle size of the functional microcapsules is 10 to 20 micrometers.
3. The graphene composite wall panel according to claim 1, characterized in that, The flame retardant is selected from one or a combination of two of ammonium polyphosphate or aluminum hydroxide; The processing aids include calcium stearate and polyethylene wax.
4. The graphene composite wall panel according to claim 1, characterized in that, The preparation method of the graphene composite wall panel includes the following steps: S1: Graphene oxide is dispersed in anhydrous ethanol, silane coupling agent KH-570 is added, and ultrasonic treatment is performed in a constant temperature water bath at 60°C. Organic functional groups are grafted through silanization reaction, and the modified graphene is obtained by centrifugation and vacuum drying. S2: Using the modified graphene as a stabilizer, the octadecane phase change core material is emulsified in an aqueous phase, and a prepolymer solution containing tourmaline and germanium powder is added dropwise. A hybrid shell is constructed by in-situ polymerization to obtain the functional microcapsules. S3: The polyurethane resin matrix, the functional microcapsules and the flame retardant are added to a twin-screw extruder and melt-blended using screw shear force at a temperature of 180°C to 200°C. The mixture is then extruded through a die and pelletized to obtain a composite masterbatch. S4: The composite masterbatch is filled into a stainless steel mold preheated to 150°C and held under pressure of 15MPa for 300 seconds to perform cross-linking and curing. After mold opening and cooling, the graphene composite wall panel is obtained.
5. The graphene composite wall panel according to claim 4, characterized in that, The preparation process of the modified graphene includes: S11: Add the graphene oxide powder to a three-necked flask containing anhydrous ethanol, and stir at a speed of 500 rpm for 30 minutes under the action of a mechanical stirrer to establish a graphene oxide dispersion. S12: Add the silane coupling agent KH-570 dropwise to the graphene oxide dispersion, place the reaction system in the constant temperature water bath, turn on the ultrasonic generator with a frequency of 40 kHz for dispersion treatment, maintain the reaction for 2 hours, and obtain the grafting reaction suspension. S13: The grafting reaction suspension was subjected to solid-liquid separation using a high-speed centrifuge at a speed of 10,000 rpm. The bottom precipitate was collected and washed three times with anhydrous ethanol. The precipitate was then dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified graphene.
6. The graphene composite wall panel according to claim 4, characterized in that, The preparation process of the functional microcapsules includes: S21: The modified graphene is added to deionized water and the pH value is adjusted to neutral. The molten octadecane phase change core material is added and sheared and dispersed for 15 minutes at a speed of 12,000 rpm using a high-shear emulsifier. A stable film is formed at the oil-water interface using the Pickering effect to obtain an oil-in-water emulsion. S22: The prepolymer solution containing the tourmaline and the germanium powder is transferred to a constant pressure dropping funnel and added dropwise to the oil-in-water emulsion under stirring at a flow rate of 5 ml per minute, while maintaining the system temperature at 50°C to obtain a mixed reaction system; S23: The mixed reaction system is heated to 85°C and the stirring speed is adjusted to 300 rpm. The reaction is maintained at this temperature for 4 hours to complete the interfacial condensation. After filtration, washing with water and spray drying, the functional microcapsules are obtained.
7. The graphene composite wall panel according to claim 4, characterized in that, The preparation process of the composite masterbatch includes: S31: The polyurethane resin matrix, the functional microcapsules and the flame retardant are added into a high-speed mixer according to the ratio, and premixed at low speed for 10 minutes at 80°C to obtain a premixed material. S32: The premixed material is added to the main feed port of the twin-screw extruder using a loss-in-weight feeder. The screw length-to-diameter ratio is set to 40:1, and the screw speed is controlled at 200 rpm. The material is sheared and melted within the specified temperature range, and then extruded through a die, cooled in a water-cooling tank, and granulated by a pelletizer to obtain the composite masterbatch.
8. The graphene composite wall panel according to claim 4, characterized in that, The preparation process of the graphene composite wall panel includes: S41: Start the heating system of the flat vulcanizing machine, preheat the stainless steel mold to 150°C, weigh and evenly spread the composite masterbatch in the mold cavity, and close the mold cover. S42: Start the hydraulic system to apply a pressure of 15MPa, maintain the pressure for 300 seconds to complete the cross-linking and curing reaction of the resin, turn on the mold cooling water circulation system to reduce the mold temperature to 60°C, open the mold and eject the product to obtain the graphene composite wall panel.
9. The graphene composite wall panel according to claim 6, characterized in that, The shell thickness control process of the functional microcapsules includes: The density of the octadecane phase change core material, the density of the hybrid shell formed by curing the modified graphene and prepolymer, and the mass ratio of the shell material to the core material were obtained. The volume ratio of the shell to the core material is calculated based on the density and the mass ratio, and the theoretical shell thickness of the functional microcapsule is derived by combining the droplet radius of the oil-in-water emulsion with the geometric volume relationship. By adjusting the dropping rate of the prepolymer solution based on the theoretical shell thickness, the functional microcapsules with uniform particle size are obtained.
10. The graphene composite wall panel according to claim 6, characterized in that, The preparation process of the prepolymer solution includes: Melamine and a 37% formaldehyde solution were added to a reaction vessel at a molar ratio of 1:
3. The pH was adjusted to 8.5 using triethanolamine. The mixture was stirred at 70°C for 30 minutes. Nanoscale tourmaline and germanium powder were then added and ultrasonically dispersed to obtain the prepolymer solution.